FORTIFIKASI TEPUNG KULIT MELINJO SEBAGAI PEWARNA ALAMI PADA PEMBUATAN KERUPUK SINGKONG - Sri Wahyuni; Muhammad Rais; Ratnawaty Fadilah (Universitas Negeri Makassar, 2017)
This study aims to identify the enhancement of cassava chips quality after the samples were added with flour made of Gnetum gnemons rind based on the data obtained from a number of panelists. The research employs CRD (Completely Randomised Design) method. The parameters tested were the level of colour, of aroma, of crispness, and of bitterness. It revealed that adding cassava flour affects the water content, the protein, the fiber, and the antioxidant. The most favourable fortification was the treatment A (combining 500gram of manioc flour porridge and 10% GnetumGnemonrind flour) with 2,6 % of water, 4.07% of protein, 6.4% offiber, and 62.73% of antioxidant.